2015
DOI: 10.1007/s11999-015-4332-8
|View full text |Cite
|
Sign up to set email alerts
|

Can Cytoprotective Cobalt Protoporphyrin Protect Skeletal Muscle and Muscle-derived Stem Cells From Ischemic Injury?

Abstract: Background Extremity trauma is the most common injury seen in combat hospitals as well as in civilian trauma centers. Major skeletal muscle injuries that are complicated by ischemia often result in substantial muscle loss, residual disability, or even amputation, yet few treatment options are available. A therapy that would increase skeletal muscle tolerance to hypoxic damage could reduce acute myocyte loss and enhance preservation of muscle mass in these situations. Questions/purposes In these experiments, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In vivo effect of antioxidant enzymes on muscle regeneration can be attributed to the increased viability of myogenic precursors under oxidative stress. Such protective potential was shown for GPX (El et al 2012 ; Lee et al 2006 ; Nishida et al 2007 ), SOD1 (Suzuki et al 2004 ), HO-1 (Kozakowska et al 2012 ; Laumonier et al 2008 ; Wilson et al 2015 ), or CAT (Catani et al 2004 ). Accordingly, decreased level of NQO1 in skeletal muscles of Nrf2 -/- aged mice was correlated with enhanced apoptosis, although it must be noted, that Nrf2 deficiency was accompanied also by decreased expression of CAT, glutathione reductase and GCS (Miller et al 2012 ).…”
Section: The Complex Role Of Oxidative Stress and Antioxidant Enzymesmentioning
confidence: 91%
See 2 more Smart Citations
“…In vivo effect of antioxidant enzymes on muscle regeneration can be attributed to the increased viability of myogenic precursors under oxidative stress. Such protective potential was shown for GPX (El et al 2012 ; Lee et al 2006 ; Nishida et al 2007 ), SOD1 (Suzuki et al 2004 ), HO-1 (Kozakowska et al 2012 ; Laumonier et al 2008 ; Wilson et al 2015 ), or CAT (Catani et al 2004 ). Accordingly, decreased level of NQO1 in skeletal muscles of Nrf2 -/- aged mice was correlated with enhanced apoptosis, although it must be noted, that Nrf2 deficiency was accompanied also by decreased expression of CAT, glutathione reductase and GCS (Miller et al 2012 ).…”
Section: The Complex Role Of Oxidative Stress and Antioxidant Enzymesmentioning
confidence: 91%
“…Aging-induced redox imbalance was associated with aggravated inflammatory reaction after acute damage (Ghaly and Marsh 2010 ). Treatment of skeletal muscle with the non-enzymatic antioxidants (Avci et al 2012 ; Myburgh et al 2012 ), GPX-mimicking compound (Gierer et al 2010 ) and finally pharmacological stimulation of SOD2 (Togliatto et al 2013 ) or HO-1 (Wilson et al 2015 ) decreased inflammation in skeletal muscle after trauma. That may in turn result in reduced muscle injury (Gierer et al 2010 ; Jazwa et al 2013 ; Li et al 2005 ; Myburgh et al 2012 ).…”
Section: The Complex Role Of Oxidative Stress and Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies suggested that Oxy can relieve the inflammatory response [ 17 , 18 ]. Thus, it is possible that Oxy treatment reduces the severity of skeletal muscle damage through an anti-inflammatory mechanism to preserve skeletal muscle function [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute limb I/R causes skeletal muscle damage due to several mechanisms [ 8 ]. Skeletal muscle is characterized by its high content of mitochondria, which has a lower threshold for ischemic damage than other tissues such as nerve or bone.…”
Section: Introductionmentioning
confidence: 99%